Luxembourg : Financial Sector Assessment Program: Technical Note-Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note reviews the stability of Luxembourg's financial system. The financial soundness indicators for Luxembourg's financial system, which plays a key role in the intermediation of financial capital, have remained relatively robust in recent years. Household stress test results suggest that households' solvency would be significantly affected by a drop in income and housing prices and a rise in unemployment. Bank liquidity displays broad resilience, but would be weakened should wholesale funding dry up or funding stress emerge in foreign currencies. Banks were found to be less vulnerable to direct contagion risk through bilateral exposure; however, most banks have considerable cross-border exposure.